Panentheism or Pansyntheism? - Gill, Jerry H. (Process studies, 2019)
My suggestion is to replace Charles Hartshorne's term "panentheism" with that of "pansyntheism" as a more fruitful way of characterizing the dynamic relation between God and the world. He introduced the term panentheism in order to split the difference between traditional theism and pantheism, to define God as highly interactive with the cosmos without being totally in control of it. The world is thought of as being in God without being identified God.